¿Qué leen los adolescentes españoles? Un estudio de los consumos de lectura analógica - Ester Trigo Ibáñez; Inmaculada Clotilde Santos Díaz; Susana Sánchez Rodríguez (Investigaciones Sobre Lectura)
This work is part of the project “Determining factors in the reading habits of secondary school students. A study from the variables of the educational context” (PR2017040), funded by the Own Research Plan of the University of Cádiz. The main objective is to know the reading consumption of Spanish teenagers. Specifically, the consumption of analog reading of students of 1st year of Compulsory Secondary Education in Spain is studied. A sample of students from the province of Cádiz (n=664) and from other Spanish provinces (n=192) responded to a questionnaire about their reading habits. It allowed, in the first instance, to determine if informants enjoy reading and, later, to gather information about what and in what format they read, the criteria on which they are based to choose their readings, how much time they dedicate to read and where they get their readings. The results indicate that this sector of the population prefers reading adventure books, chooses books by subject, reads more during holidays and uses their own books. However, it is confirmed that the development of the reading habit is still a subject to pass.